BMI Patient Injury Anterior Cruciate Ligament (ACL) Post Operative And Conservative Action - Bhekti Lestari; Damayanti Tinduh; Ria Lumintuarso (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Body Mass Index (BMI) is on of most risk factors for ACL injury. Operative treatment and conservative treatment are the exact solution for handling ACL injuries. The aim of this study is to determine the difference of mean Body Mass Index (BMI) in patients with ACL injury post operative and conservative treatments. Type of this research was observational with post test only design and used a cross-sectional approach. Fifteen operative patients and fifteen conservative patients were selected based on inclusion and exclusion criteria, divided into OT (Operative Treatment) and KT(Conservative Treatment) groups. Body weight and body height measurements were carried out to obtain Body Mass Index (BMI). The results obtained by means and p value are OT group 24,59 ± 5,00 Kg/m² > KT group 23,49 ± 2,60 Kg/m² (p= 0,256 > 0,05). The results can be concluded that there is no significant difference BMI between OT and KT group